PENGARUH PENGGUNAAN APLIKASI TIKTOK TERHADAP PERILAKU KECANDUAN SISWA SISWI SEKOLAH MENENGAH ATAS DI KOTA BATAM - Malau, Novita Octavia Mardalena; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2022)
Today's social media developments are changing the behavioral patterns of individuals. Oneof these social media is the Tiktok application. The application is currently favored by a widevariety of groups, from adults to teenagers to children. The purpose of this study is todetermine whether the use of the Tik-Tok application influences the addictive behavior ofhigh school students in Batam City. The research method used is a quantitative method.The study population was high school students from Batam City using a random samplingmethod. Data analysis techniques used descriptive statistical tests, classical hypothesistesting, simple linear regression, and hypothesis testing. From the simple linear regressionresults, the regression equation Y = 3.482 + 1.149 X has a positive effect between variableusage (X) and dependent behavior (Y) in the Tiktok application